Characterization of a P-selectin-binding moiety from Bupleurum chinense polysaccharide and its antagonistic effect against P-selectin-mediated function. (15th September 2018) - Tong, Haibin; Wu, Siya; Song, Kangxing; Liu, Jian; Song, Xindan; Zhang, Xu; Huang, Luqi; Wu, Mingjiang
Highlights: We prepared an P-selectin-binding affinity chromatography media. A P-selectin-binding moiety of BCPS was isolated and designated as BCPS-m. BCPS-m possessed stronger antagonistic effect against P-selectin. BCPS-m could be the key functional moiety antagonizing P-selectin in BCPS. Abstract: P-selectin is a promising therapeutic target for acute inflammation-related diseases, and interest has been growing in the search for high-affinity glycoconjugate ligands that can target the initial P-selectin-mediated recruitment of neutrophils to the site of inflammation. In our previous study, we isolated a water-soluble polysaccharide (BCPS) from Bupleurum chinense and showed that it exhibits anti-inflammatory effect by antagonizing P-selectin-mediated adhesion of HL-60 cells to CHO-P cells. In this study, we prepared a P-selectin-based affinity chromatography medium and used it to purify the P-selectin-binding moiety of BCPS. The purified P-selectin-binding moiety of BCPS, designated as BCPS-m, was mainly composed of arabinose, galactose and glucose, and had a relative molecular weight of 3600 Da. The backbone of BCPS-m was composed of 1, 5-linked arabinose, 1, 4-linked and 1, 4, 6-linked glucose, and with branched 1-linked glucose or galactose terminal. BCPS-m could disrupt the P-selectin-mediated binding of HL-60 cells to CHO-P cells (CHO cells that stably expressed an exogenous P-selectin). It also blocked the interaction between P-selectin and its physiological ligand PSGL-1 significantly, resulting in much greater reduction (77%) in P-selectin-PSGL-1 binding than that caused by BCPS (35%). The data suggested that BCPS-m could be the key P-selectin-binding moiety of BCPS, and that it may be a better P-selectin antagonist than BCPS.